2011
DOI: 10.1155/2011/698248
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Enteral Nutrition and Total Parenteral Nutrition in Patients with Acute Pancreatitis

Abstract: Objective. To analyze the effect of total parenteral nutrition (TPN) and enteral nutrition (EN) in patients with acute pancreatitis. Methods. Randomized controlled trials of TPN and EN in patients with acute pancreatitis were searched in NCBI and CBM databases and The Cochrane Controlled Trials Register. Six studies were enrolled into the analysis, and the details about the trial designs, characters of the subjects, results of the studies were reviewed by two independent authors and analyzed by STATA 11.0 soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 35 publications
2
18
0
1
Order By: Relevance
“…Several clinical studies have demonstrated that EEN can produce better clinical outcomes than TPN . Consistent with these studies, we found that EEN treatment resulted in a higher survival rate in SAP rats compared with TPN, accompanied by a decreased in the serum amylase content.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several clinical studies have demonstrated that EEN can produce better clinical outcomes than TPN . Consistent with these studies, we found that EEN treatment resulted in a higher survival rate in SAP rats compared with TPN, accompanied by a decreased in the serum amylase content.…”
Section: Discussionsupporting
confidence: 90%
“…However, several studies have shown that TPN is associated with disrupted gut‐barrier function, comprised immune system, and increased bacterial translocation . In contrast, increasing evidence has shown that enteral nutrition (EN) improves overall patient outcome compared with TPN . Furthermore, early EN (EEN) has been reported to be associated with reduced complications and improved clinical outcomes in AP patients .…”
Section: Introductionmentioning
confidence: 99%
“…After surgery small bowel recovers its ability to absorb nutrients almost immediately . There are evidences that the early enteral feeding has been shown to preserve the integrity of gut mucosa and to keep up its immunological function . After the esophagectomy, the intestinal ischemia or intestinal paralysis and lack of the intestinal stimulation and oral nutrition can increase the atrophy, damage the permeability of intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…4 There are evidences that the early enteral feeding has been shown to preserve the integrity of gut mucosa and to keep up its immunological function. [27][28][29] After the esophagectomy, the intestinal ischemia or intestinal paralysis and lack of the intestinal stimulation and oral nutrition can increase the atrophy, damage the permeability of intestinal mucosa. As a result, the gut bacteria and endotoxins can easily migrate and enter the blood stream.…”
Section: Discussionmentioning
confidence: 99%
“…In two following meta-analysis these conclusions proved to be correct [19,20]. In the latest meta-analysis published by Heming in 2012 [21], six studies were reviewed comparing EN vs PN and it becomes clear that nutritional support with EN decreases pancreatic complications (infections, abscesses and necrosis), mortality rate and multi-organ failure. Concerning infective complications with a non-pancreatic origin, including pneumonia, urinary tract infection and catheter infection, there were not significant differences.…”
Section: Severe Apmentioning
confidence: 97%